Search for higgs bosons decaying to tau pairs in pp̄ collisions with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We present a search for the production of neutral Higgs bosons decaying into τ+τ- final states in pp̄ collisions at a center-of-mass energy of 1.96 TeV. The data, corresponding to an integrated luminosity of approximately 1fb-1, were collected by the D0 experiment at the Fermilab Tevatron Collider. Limits on the production cross section times branching ratio are set. The results are interpreted in the minimal supersymmetric standard model yielding limits that are the most stringent to date at hadron colliders. © 2008 The American Physical Society.